PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALIITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (STUDY EMPIRIS PADA BPKP SEMARANG) - Fitri Wahyu Nisviana, 12.05.52.0071; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2016)
The objectived of this reserarch to empirically analyze the influence of competency and independency on audit quality, and to the influence of competency and independency to audit qualityncy is moderated by auditor ethics, especially in the internal auditor (APIP) working in BPKP Semarang. The population in this research are all auditors who worked on the BPKP in Semarang. Sampling was conducted using a purposive sampling method and number of samples of 73 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using technical analy Moderate Regression Analyze ( MRA ).The result indicate the competence of auditors significant positive effect on the quality of auditors, Interaction competence of auditors with auditors ethics as a moderating variable significant negative effect on the quality of auditors,the auditor’s independence significant positive effect on the quality of auditors, Interaction independence of auditors with auditors ethics as a moderating variable significant positive effect on the quality of auditors.Keywords: Competency, Independency, Auditors Ethics, Quality Of Audit